Biocontrol potential and underlying mechanism of Trichoderma asperellum C15 against postharvest anthracnose of chili pepper - Jie Zhong; Rui Guo; Jia Rui Yang; Jin Chen; Xiao Gang Li; Jun Zi Zhu (Postharvest Biology and Technology, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Nonradical pathway in peroxymonosulfate-based Fenton-like reactions triggered by the active Fe-Cu dual sites encapsulated in endogenous N-rich biochar - Rui Yang; Chaoting Jiang; Wangbo Wang; Xianshu Zhou; Fangshu Xie; Mingming Ta; Tuo Wang; Haifang Cai; Juan Guo; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Soil deposition reduces bacterial network complexity and stability by shifts in life-history strategies on the Loess Plateau of China - Yanqing Guo; Hailun Zhang; Shunxiang Yao; Bin Zhu; Rui Ma; Xiuling Li; Qianjin Liu; Qiqi Sun; Shengli Guo; Yaxian Hu; Lanlan Du (Applied Soil Ecology, 2026)

Copper-doped Coptidis Rhizoma-derived carbon dots (Cu-CR-CDs) nanozymes exhibit intestinal protective effects against Escherichia coli-induced diarrhea - Hongrui Guo; Rui Du; Zijing Dai; Zhidi Xu; Yanqiu Zhu; Xianxiang Wang (Food Bioscience, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Resistome risks of biological wastewater treatment communities: A global dataset of activated sludge, anaerobic digestion, and anammox - Min Xu; Shengchun Qi; Xiaofan Yu; Shiyi Han; Rui Xiao; Jianhua Guo; Changzhi Wang; Ning Zhu; Huijie Lu (Journal of Hazardous Materials, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Sustainable land use and agricultural management enhance arbuscular mycorrhizal fungal communities and soil health - Huaisong Wang; Juntong Zhu; Mingming Wang; Lei Zhang; Ying Gao; Lianxuan Shi; Jixun Guo; Rui Guo; Tao Zhang (Applied Soil Ecology, 2026)

Quantification of 3D Fracture Network Characterization and the Coupling Mechanisms in Non-blasting SC-CO2 Fracturing: A Bayesian Calibrated Multiscale Complex Fracture Index - Chao Zhu; Jie Chen; Zhonghao Luo; Kunyong Guo; Wenhao Shi; Yuanyuan Pu; Yichao Rui; Deping Guo (Rock Mechanics and Rock Engineering, 2026)

Phosphogypsum coupled enzyme-induced calcium carbonate precipitation for soil stabilization: Mechanical performance and sustainable application - Lun Zhang; Yun Dai; Zhenyao Xia; Jun Wu; Zhien Zhu; Yunkang Rao; Hongqiang Shi; Chao Kang; Rui Xiang; Hongwei Guo; Hai Xiao (Journal of Environmental Management, 2026)

Mechanistic insights into polystyrene micro/nanoplastics-facilitated cadmium trophic transfer and aggravated toxicity along a lettuce-snail terrestrial food chain - Fuyu Guo; Bo Xu; Rui Zhang; Yan Chang; Tingting Chu; Meng Zhu; Fengxiang X. Han; Ruyi Yang (Environmental Pollution, 2026)

How well do street view images predict crime rates in London? A comparison with social and macro-level environmental features - Sitong Guo; Richard Harris; Rui Zhu (Computers, Environment and Urban Systems, 2026)

Biomimetic sequential immuno-osteogenic regulation via a dual-drug delivery system with PDA coating on sulfonated PEEK promotes bone defect repair - Zixuan Wu; Kai Ma; Xiaoyu Guo; Zidong Wu; Zheyue Zhu; Yuning Qu; Weidong Zhu; Chengxin Li; Rui Ma; Pei Yang (Chemical Engineering Journal, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Parallelization of the estuarine saltwater intrusion numerical forecast model UFDECOM-i using Fortran DO CONCURRENT - Hongyuan Guo; Bingrui Chen; Rui Ma; Yihe Wang; Jianrong Zhu (Environmental Modelling & Software, 2026)

Elucidating the complex food sources and biomagnification of hydrophobic and proteinophilic persistent organic pollutants in wetland birds from a tropical island - Yujing Zhu; Bei Cai; Jichao Wang; Rui Guo; Li Jian; Xiaobo Zheng; Bixian Mai (Journal of Hazardous Materials, 2026)

Enhanced degradation of microplastics by laccase under ambient conditions: Analysis of underlying molecular mechanisms - Rui Ding; Linhan Xu; Xiaoling Shan; Xinran Qiu; Ling Ding; Bin Zhang; Xujun Liang; Lingyan Zhu; Xuetao Guo (Journal of Hazardous Materials, 2026)

Genetic Parameter Estimation of Growth Traits and Their Implications for Selective Breeding in Small Yellow Croaker (Larimichthys Polyactis) - Rui Wang; Jiajie Zhu; Sifang Liu; Ting Ye; Dandan Guo; Yang Liu; Bao Lou; Feng Liu (Marine Biotechnology, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Influences of topography changes on the evolution of salinity intrusion in the North Branch of the Yangtze River Estuary over the past 70 years - Rui Ma; Zhilin Zhang; Yidi Yang; Zhigang Guo; Jianrong Zhu; Yihe Wang (Frontiers in Marine Science, 2026)
Estuarine topography influences hydrodynamics and salinity intrusion. The most significant feature of salinity intrusion in the Yangtze River Estuary is the salt-spilling-over (SSO) into the South Branch from the North Branch (NB), which affects the utilization of freshwater resources in the South Branch where three reservoirs were built. The topography in different decades from the 1950s to the 2020s was collected, and a numerical model was adopted to simulate the topography changes on salinity intrusion and SSO. From the 1950s to the 2020s, the topography of the Yangtze River Estuary changed greatly, especially in the NB. The channel area of the NB decreased by 55.56%, and its channel volume decreased by 57.57%. The numerical simulation results showed that the evolution of salinity intrusion in the NB and SSO experienced weakening–enhancing–weakening processes. The NB was covered by high-salinity water and experienced the SSO in the 1950s. The SSO distinctly weakened in the 1970s and 1980s, greatly enhanced in the 1990s, reached its most severe level in the 2000s, and significantly weakened in the 2010s and 2020s. From the 1950s to the 2020s, the tidal prism of the NB constantly decreased, with a reduction of 62.32% during spring–neap tide. The variations in the net water flux, net salt flux, and water diversion ratio in the upper section of the NB were consistent with the evolution processes of SSO. The evolution mechanisms of the salinity intrusion and SSO were elucidated in view of changes in the estuarine topography and dynamic factors.

Cadmium immobilization and selenium mobilization by Citrobacter freundii in soil-rice system: a trade-off between remediation efficacy and soil microbial community integrity - Fuyu GUO; Tianao YU; Rui ZHANG; Tingting CHU; Meng ZHU; Shuting ZAN; Fengxiang X. HAN; Ruyi YANG (Pedosphere, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Quantifying the vulnerability of karst groundwater to emerging organic compounds in southwest China - Rui An; Bin Li; Jie Li; Shengpin Li; Qianying Zhu; Xiaoyu Liu; Huaming Guo; Wenpeng Li; Kun Liu (Environmental Pollution, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

The association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with surrogate indicators of insulin resistance: a panel study - Sha You; Lin Liu; Min Xiang; Lei Zhao; Wenting Guo; Xiaomin Zhang; Rui Zhu; Liangle Yang (Environmental Geochemistry and Health, 2026)

Deciphering the core microbiomes and associated genes and metabolites during the Shanxi aged vinegar making process - Rui Ma; Mingxia Cheng; Qiong Zhou; Xiaojie Nan; Min Zhu; Shang Guo; Zhibin Zhang; Fang Gao; Jingang Gu (Food Bioscience, 2025)

Engineering V-based Prussian blue analogue cathodes toward ultrahigh capacity and rate capability in aqueous zinc-ion batteries - Yan Chen; Na Shen; Xinyu Guo; Chang Li; Chengcheng Zhu; Nan Jiang; Xi Liu; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2025)

Protection against intestinal damage in female Drosophila melanogaster: Comparative contribution of arabinoxylan and its non-covalent/covalent complexes with catechin - Dima Atehli; Tianyu Qi; Rui Liu; Wan Wang; Qiaomei Zhu; Yuanlin Sun; Qingbin Guo; Ji Kang (Bioactive Carbohydrates and Dietary Fibre, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Genetic sensitivity moderates the effects of joint exposure to air pollution on depression risk: a genome-wide by environment interaction analysis - Yaoyao Sun; Xue Lv; Wenjian Bi; Yuyanan Zhang; Zhe Lu; Jing Guo; Zhewei Kang; Xiaoyang Feng; Yundan Liao; Guorui Zhao; Junyuan Sun; Yang Yang; et al. (Environmental Pollution, 2025)

Phytosphingosine suppresses gastric cancer through SFRP4/β-catenin axis-mediated Wnt signaling pathway inhibition - Yanchen Liu; Rui Guo; Chi Xue; Xinwei Zhang; Fanghao Xiao; Xiangxuan Zhao; Zhi Zhu; Kai Li (Chemico-Biological Interactions, 2025)

Self-sustaining one-step synergy of ultrasound-enzyme-ethanol for high-efficiency saponin production from waste Xanthoceras sorbifolium leaves - Huan Long; Rui Guo; Wangsheng Zhu; Fuliang Cao; Erzheng Su; Jiahong Wang (Biomass and Bioenergy, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Silkworm sand-based bio-organic fertilizers reshape rhizosphere microbiomes and modulate soil chemistry for sustainable management of Myrica rubra decline - Leidong Hong; Chunlai Hong; Weijing Zhu; Fengxiang Zhu; Weiping Wang; Tao Zhang; Rui Guo; Xingjiang Qi; Xiuqin Zou; Yanlai Yao (Plant and Soil, 2025)

Quantitative relationship between unsuitable water intake time at Qingcaosha reservoir and river discharge under different northerly wind speeds - Xinyi Guo; Rui Ma; Jianrong Zhu (Frontiers in Marine Science, 2025)
Estuarine saltwater intrusion is mainly controlled by river discharge, tide and wind. It is important for utilization of estuarine freshwater to study quantitative relationship between unsuitable water intake time and river discharge. A two-way nested unstructured quadrilateral grid, finite-differencing, three-dimensional estuarine and coastal ocean model (UFDECOM-i) was applied to simulate the saltwater intrusion in the Changjiang Estuary and to get the quantitative relationship between unsuitable water intake time at Qingcaosha Reservoir and river discharge under different northerly wind speeds. The results of numerical experiments show that the salinity at the water intake of Qingcaosha Reservoir is very sensitive to the variation in river discharge. Under 7 day northerly wind of 10 m/s, when the river discharge is 8000 m 3 /s, the entire estuary is occupied by saline water; the net unit width salt flux (NUSF) landward flows in the North Channel, then flows into the South Channel toward sea, forming a horizontal salt transport route of “flowing into the North Channel and out in the South Channel” due to the strong landward Ekman transport. When the river discharge is 12000 m 3 /s, the horizontal salt transport route is weakened with the increase of river discharge. Under 7 day northerly wind of 15 m/s, saltwater intrusion increases significantly with the increase of wind speed, and the pattern of NUSF become much stronger. The salinity increases enormously after the action of persistent strong northerly wind. The quantitative relationship between river discharge and the longest continuous unsuitable water intake time of Qingcaosha Reservoir is expressed by formula under climatic wind, 7 day northerly wind of 10 m/s and 15 m/s, respectively, with correlation coefficient R 2 of greater than 0.97, which can provide a basis for reservoir water intake and water supply safety.

Unraveling the impact of COVID‑19 on Beijing’s subway system using a causal machine learning analysis - Linmu Zou; Yanhua Chen; Rui Guo; Peicheng Wang; Yanrong He; Shiyu Chen; Zijia Wang; Jiming Zhu (Sustainable Cities and Society, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Contrasting leaf nutrient-hydraulic relationships between karst and non-karst forests - Chun-Yan Wan; Jun-Rui Yu; Zhong-Guo Li; Yong-Qiang Wang; Shi-Dan Zhu (Plant and Soil, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

An automatic landmarking algorithm for leaf morphology based on conformal mapping - Peige Zhong; Xiaojun Liu; Yulu Ye; Rui Zhang; Hu Zhou; Yan Guo; Baoguo Li; Jinyu Zhu; Yuntao Ma (Computers and Electronics in Agriculture, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Tailoring porous carbon from optimized coal blends for high-performance supercapacitor electrodes - Yanli Zhu; Tao Wang; Yan Ma; Rui Sheng; Pengxu Ren; Jia Guo; Dianzeng Jia; Dongling Wu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

ANAC050 confers aluminium resistance by cooperating with secretion of organic acids and accumulation of cell wall hemicelluloses in plants - Ye TAO; Su LI; Yusong LIU; Rui GUO; Changzhao CHEN; Jiu HUANG; Qiang ZHANG; Renfang SHEN; Xiaofang ZHU (Pedosphere, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Intelligent identification and semantic segmentation of deep rock fracture based on deep ensemble learning and transfer learning - Rui Li; Qingsong Zhang; Shaoxuan Guo; Guangxuan Zhu; Hongzhao Li; Xin Chen; Junlong Yan (Tunnelling and Underground Space Technology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Species-specific accumulation of microplastics in different bird species from South China: A comprehensive analysis - Ying Zeng; Junjie Cai; Yujing Zhu; Jichao Wang; Rui Guo; Li Jian; Xiaobo Zheng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Interval prediction of fuel cell degradation based on voltage signal frequency characteristics with TimesNet-GPR under dynamic conditions - Wenchao Zhu; Yongjia Li; Yafei Xu; Leiqi Zhang; Bingxin Guo; Rui Xiong; Changjun Xie (Journal of Cleaner Production, 2025)

Solve the cause, not the symptom: Managerial myopia and environmental investment preferences - Rui Zhu; Yalan Zhang; Huixiang Zeng; Lian Guo (Journal of Environmental Management, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Influence of edge scour on lateral responses of monopiles with precast microbial reinforcement - Siyuan He; Jinhai Zheng; Rui He; Seyed Mohammad Javad Hosseini; Tao Zhu; Liang Cheng; Zhen Guo (Ocean Engineering, 2024)

Effect of clayey sediment compression on fluoride enrichment in the Quaternary groundwater system of Cangzhou Plain, China - Rui Liu; Haipeng Guo; Juan Chen; Haigang Wang; Xisheng Zang; Guijie Wang; Yunlong Wang; Juyan Zhu (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Biocontrol potential of Bacillus velezensis HG-8-2 against postharvest anthracnose on chili pepper caused by Colletotrichum scovillei - Jie Zhong; Xiao Wu; Rui Guo; Jiaxin Li; Xiaogang Li; Junzi Zhu (Food Microbiology, 2024)

Deciphering the biodegradation mechanism of 3,6-dichlorocarbazole using a novel isolate for its implication in bioaugmentation - Mi Feng; Rui Zhou; Zhaolong Zhu; Yantian Xie; Minghan Zhu; Zhanyu Guo; Xinghui Feng; Dongxia Fu; Jianhua Chen; Yanhong Du; Yao Huang (Chemical Engineering Journal, 2024)

Deciphering the nonlinear and synergistic role of building energy variables in shaping carbon emissions: A LightGBM- SHAP framework in office buildings - Congyue Zhou; Zhu Wang; Xuanli Wang; Rui Guo; Zhao Zhang; Xingwei Xiang; Yiqun Wu (Building and Environment, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Disruption of a glycosyl transferase family 17 protein alters cadmium accumulation and resistance in rice (Oryza sativa) - Chun Yan Tu; Rui Guo; Chang Zhao Chen; Yong Qiang Gao; Lu Zheng; Qiang Zhang; Ren Fang Shen; Xiao Fang Zhu (Plant and Soil, 2024)

Association of the COL4A2 Gene Polymorphisms with Primary Intracerebral Hemorrhage Risk and Outcome in Chinese Han Population - Huan Wang; Yuyi Zhu; Lukai Zheng; Mingxi Chen; Zilong Hao; Rui Guo; Ling Feng; Deren Wang (Molecular Neurobiology, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Multifunctional-Element doping of NASICON-Structured cathode enables High-Rate and stable sodium storage - Xi Liu; Chengcheng Zhu; Tianhe Xu; Chang Li; Xinyu Guo; Nan Jiang; Yan Chen; Yushuang Xu; Runduo Zhu; Wenxia Zou; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Influence of precast microbial reinforcement on lateral responses of monopiles - Tao Zhu; Rui He; Seyed Mohammad Javad Hosseini; Siyuan He; Liang Cheng; Yakun Guo; Zhen Guo (Ocean Engineering, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Geogenic high arsenic elevates the groundwater antibiotic resistomes: A blind spot of resistance in Anthropocene - Rui Xu; Lingzhi Zhang; Fu-Yi Huang; Yong-Guan Zhu; Yi Zhao; Huaming Guo (Water Research, 2024)

Novel insights into the relationship between the functional groups and photoactivity of biochar-derived dissolved organic matter - Xin Zuo; Zhuozhi Ouyang; Jinmo Liao; Rui Ding; Weiwei Zhang; Chi Zhang; Xuetao Guo; Lingyan Zhu (Water Research, 2024)

Lithofacies, architecture and evolution of carbonate tidal delta system: Implications for reservoir heterogeneity (mid-cretaceous Mishrif Formation, Southeast Iraq) - Xiaowei Sun; Zhanfeng Qiao; Rui Guo; Guangya Zhu; Jianyong Zhang; Guanming Shao; Yu Zhang; Haiying Han; Zhehang Xu (Marine and Petroleum Geology, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Understanding secondary particles in a regional site of Yangtze River Delta: Insights from mass spectrometric measurement - Wenfei Zhu; Jialin Shi; Hui Wang; Ying Yu; Rui Tan; Ruizhe Shen; Jun Chen; Shengrong Lou; Min Hu; Song Guo (Science of The Total Environment, 2024)

Corrigendum to “Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa)” J Hazard Mater 469(2024) 133862 - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

Body size: A hidden trait of the organisms that influences the distribution of antibiotic resistance genes in soil - Rui Guo; Yanlai Yao; Zhe Zhang; Chunlai Hong; Fengxiang Zhu; Leidong Hong; Weijing Zhu (Journal of Hazardous Materials, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Multifunctional BiOBr/BiOI 3D microspheres for improving visible-light-driven photocatalytic degradation and disinfection efficiency - Saifeng Zhang; Jian Guo; Saisai Deng; Rui Zhang; Qiuyu Zhu; Yuanxu Liu; Xiangang Lin; Yangyang Li (Journal of Environmental Chemical Engineering, 2024)

High variation of worker cell and morphology between two adjacent populations of honey bee, Apis cerana (Hymenoptera, Apidae) - Rui Zhu; Weilai Zhong; Yuhui Chen; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Method of characteristics with a new Macro-track transport acceleration for complex general geometry - Guo Jian; Zhu Guifeng; Yan Rui; Zou Yang (Annals of Nuclear Energy, 2024)

Unveiling of dietary and gut-microbiota derived B vitamins: Metabolism patterns and their synergistic functions in gut-brain homeostasis - Qi Zhan; Rui Wang; Kiran Thakur; Jing-Yu Feng; Yun-Yang Zhu; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa) - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

Effects of ultrasonic treatment on the texture quality of aged rice flour - Yubao Guo; Rui Song; Shimin Zhu; Xinyu Liu; Xinyu Wang (Journal of Cereal Science, 2024)

Effect of nano-SiO2 modification on the seismic performance of recycled aggregate concrete shear walls - Yingwu Zhou; Liu Fan; Feng Xing; Wenwei Lin; Rui Hu; Menghuan Guo; Zhongfeng Zhu (Engineering Structures, 2024)

Field implementation to resist coastal erosion of sandy slope by eco-friendly methods - Yujie Li; Zhen Guo; Lizhong Wang; Yongqiang Zhu; Shengjie Rui (Coastal Engineering, 2024)

The toxicity of polystyrene micro- and nano-plastics on rare minnow (Gobiocypris rarus) varies with the particle size and concentration - Tingting Chu; Rui Zhang; Fuyu Guo; Meng Zhu; Shuting Zan; Ruyi Yang (Aquatic Toxicology, 2024)

Chlorogenic acid improves common carp (Cyprinus carpio) liver and intestinal health through Keap-1/Nrf2 and NF-κB signaling pathways: Growth performance, immune response and antioxidant capacity - Guo-Jun Shang; Si-ying Liu; Rui Zhu; Deng-Lai Li; Si-Tong Meng; Yin-tao Wang; Li-Fang Wu (Fish & Shellfish Immunology, 2024)

Water Properties and Diffusive Convection in the Canada Basin - Ling Qu; Shuangxi Guo; Shengqi Zhou; Yuanzheng Lu; Mingquan Zhu; Xianrong Cen; Di Li; Wei Zhou; Tao Xu; Miao Sun; Rui Zeng (Journal of Marine Science and Engineering, 2024)
The aim of this study is to better understand diffusive convection (DC) and its role in the upper ocean dynamic environment and sea ice melting in the Canada Basin. Based on a moored dataset with 6737 profiles collected from August 2003 to August 2011 in the upper layer of the Canada Basin, DC between the warm and salty Atlantic Water (AW) and the colder and less salty Lower Halocline Water (LHW) were investigated. The moorings were designated at four stations: A, B, C, and D, located at the southwestern, southeastern, northeastern, and northwestern parts of the basin, respectively. During the observation period, the temperature, salinity, and depth of the AW and LHW exhibited unique temporal variations. The temperature and salinity of the AW varied among stations, with a decreasing trend from northwest to southeast, consistent with the propagation path of the AW in the Canada Basin. The temperature and salinity of the LHW were similar at all stations. The AW and LHW cores were located between depths of 320–500 m and 160–300 m, respectively, and both gradually deepened over time. Distinct DC staircase structures were observed between the AW and LHW, more pronounced at stations C and D than at stations A and B, which is speculated to be related to eddies at stations A and B during the observation period. The vertical heat fluxes through the DC staircase layer at stations C and D (FHc_C and FHc_D) were estimated using an empirical formula. FHc_C ranged from 0.05 to 0.94 W/m2, and FHc_D ranged from 0.05 to 0.6 W/m2, with the maximum probability value for both at approximately 0.2 W/m2. The effective diffusivities at these two stations (KT_C and KT_D) are similar, ranging from 2 × 10−6 to 3 × 10−5 m2/s, with the highest probability occurring at 6 × 10−6 m2/s. Both the probability density function of the heat flux and the effective diffusivity skewed towards larger values and obey a lognormal distribution, indicating turbulence intermittency of the DC staircase in the Canada Basin. These finding offers new insights into the heat transport and turbulence in the DC staircase, and then bring a deeper understanding of sea ice melting in the Canada Basin.

Spatial distribution characteristics of perfluoroalkyl substances in bulk and grain size fractionated sediments in Shenzhen Bay - Haoshuai Li; Zimin Wang; Yang Zhou; Cui Shi; Huayang Gan; Fang Chen; Lei Xing; Danxu Guo; Longhai Zhu; Nan Wang; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2024)

How carbon trading influences manufacturing/remanufacturing? A coordination mechanism design based on outsourced remanufacturing - Jingyuan Guo; Rui Wu; Wei Wang; Weidi Zhu (Journal of Cleaner Production, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)

Automatic detection of crop lodging from multitemporal satellite data based on the isolation forest algorithm - Rui Guo; Xiufang Zhu; Tingting Liu (Computers and Electronics in Agriculture, 2023)

Potential of a winterschmidtiid prey mite for the production of the predatory mite Neoseiulus californicus (Acari: Phytoseiidae) - Rui Zhu; Jian-jun Guo; Tian-ci Yi; Fei Hou; Dao-chao Jin (Experimental and Applied Acarology, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Trehalose metabolism targeting as a novel strategy to modulate acid tolerance of yeasts and its application in food industry - Zhongpeng Guo; Moying Li; Zitao Guo; Rui Zhu; Yu Xin; Zhenghua Gu; Liang Zhang (Food Microbiology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Anti-hardening effect and mechanism of silkworm sericin peptide in high protein nutrition bars during early storage - Hongtao Zhu; Xiu-Xiu Zhang; Rui Zhang; Jing-Yu Feng; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Characteristics of silicon and phytolith distribution in bamboo (Ferrocalamus strictus): variations between different organs and ages - Rui Xu; Honglan He; Huijun Guo; Fangwei Zhu; Shuguang Wang; Cefeng Dai; Xiaofeng Zheng; Dongbo Xie; Haoming Li; Changming Wang; Hui Zhan (Review of Palaeobotany and Palynology, 2023)

C3-symmetric trimeric imidazole naphthoquinone derivative with dual redox-active sites for high-performance cathodic lithium storage - Yifang Zhu; Wei Jin; Haiguang Gao; Yanli Chen; Tai-Rui Wu; De-Yin Wu; Yucheng Huang; Dengfeng Guo; Zhidong Chen; Qinghong Huang; Jianyu Cao; Juan Xu (Chemical Engineering Journal, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

A model description of beta oscillations in the external globus pallidus - Mingming Chen; Yajie Zhu; Rui Zhang; Renping Yu; Yuxia Hu; Hong Wan; Dezhong Yao; Daqing Guo (Cognitive Neurodynamics, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Experimental Study of Vibration Reduction Effect of Barrier Holes Under Blasting - Jianbo Zhu; Rui Zhao; Yashi Li; Yankun Ma; Jianxin Wang; Qi Peng; Jun Guo (Rock Mechanics and Rock Engineering, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Human Urine-Derived Stem Cells Improve Partial Bladder Outlet Obstruction in Rats: Preliminary Data and microRNA-mRNA Expression Profile - Menjiang Tu; Rui Wang; Pei Zhu; Qingqing Wang; Bishao Sun; Keshi Lu; Jiawei Zhang; Weijie Xie; Huan Guo; Shulin Li; Yuqi Wu; Xiangwei Wang (Stem Cell Reviews and Reports, 2022)
Partial bladder outlet obstruction (pBOO) often results in bladder tissue inflammation and remodeling. As human urine-derived stem cells (USCs) have demonstrated therapeutic benefits, we used a rat model to investigate the effect of USCs on bladder function and explore the miRNA and gene expression profiles in bladder tissue using RNA sequencing. Eighteen rats were assigned to a sham surgery group, pBOO group, and pBOO+USC group (six biweekly treatments). Routine urodynamic monitoring, analysis of detrusor muscle strips, and pathophysiology assessments were conducted. Finally, altered miRNA and mRNA expression profiles of bladder tissue were examined using RNA sequencing and bioinformatics analysis. After USC treatment, elevated bladder compliance and maximal voiding pressure, declined end filling pressure and voided volume, and improved detrusor muscle contractility and carbachol sensitivity were found. Histology and TUNEL assay revealed reduced collagen deposition and muscle cell apoptosis in bladder tissue. The differential expression of eight miRNAs was reversed by USC treatment. Two large nodes (miR-142 and miR-9a) were identified in the miRNA-gene interaction network in the USC-treated group. The Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment of multiple significant pathways, including those involved in necroptosis and cytokine-cytokine receptor interactions. This is the first study to demonstrate the protective effect of USCs on bladder function and remodeling in pBOO rats. The miRNA and mRNA expression levels differed in the bladder of pBOO rats with and without USC treatment. Although the mechanism underlying these effects has not been fully elucidated, necroptosis and cytokine-cytokine receptor interaction-related pathways may be involved. Graphical abstract

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Ri Jin Jiang; Fan Yang; Feng Chen; Rui Yin; Ming Zhi Liu; Wen Bin Zhu; Ai Guo; Lian Wei Liu (Frontiers in Marine Science, 2022)
Trophic research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 103 bigeye tuna ( Thunnus obesus ), 296 yellowfin tuna ( Thunnus albacores ), and 264 albacore tuna ( Thunnus alalunga ) samples were collected from September to December 2019. Samples for stomach content and stable isotope analysis were randomly selected. The stomach content analysis results showed that the stomach contents of the three tuna species were rich in prey, and 48 prey species were identified, including fish, cephalopods, and crustaceans, with high between-phenotype component (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity of bigeye tuna were higher than that of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate (35.69%) and lowest average stomach fullness index (0.064). The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant ( P <0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. Bigeye tuna mainly feed on Ommastrephes bartrami and Myctophidae, yellowfin tuna mainly feed on Hyperiidea and Aluterus monoceros , and albacore tuna mainly feed on Gempylus serpens and Loligo chinensis . The stable isotope results showed that the δ 13 C and δ 15 N values of the three tuna species were significant ( P <0.001). The standard ellipse area corrected for small sample sizes (SEAc) and total niche area (TA) of bigeye tuna, range of δ 15 N (NR) of yellowfin tuna, and range of δ 13 C (CR) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Roseococcus pinisoli sp. nov., lacking pufL and pufM bacteriochlorophyll a: synthesizing genes - Lei Shen; Miao-miao An; Rui-na Liang; Peng-xiao Liu; Xiang-wei He; Guo-zhu Zhao (Archives of Microbiology, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

Nitrogen and carbon addition changed nitrous oxide emissions from soil aggregates in straw-incorporated soil - Junhui Yin; Rui Liu; Wenchao Cao; Kun Zhu; Owen Fenton; Jingheng Guo; Qing Chen (Journal of Soils and Sediments, 2022)

A comparison of hepatotoxicity induced by different lengths of tungsten trioxide nanorods and the protective effects of melatonin in BALB/c mice - Lin Mao; Lifang Zheng; Huihui You; Muhammad Wajid Ullah; Haoyan Cheng; Qing Guo; Zhihong Zhu; Zhuge Xi; Rui Li (Environmental Science and Pollution Research, 2021)

Photocatalytic purification of vehicle exhaust using CeO2–Bi2O3 loaded on white carbon and tourmaline - Yanqiu Bi; Rui Li; Fucheng Guo; Chundong Zhu; Jianzhong Pei (Environmental Science and Pollution Research, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Depositional and diagenetic controls on the reservoir quality of Upper Triassic Chang-7 tight oil sandstones, southwestern Ordos basin, China - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Zhuopei Li; Yangjinfeng Jiang; Xueqi Yang; Rui Xie; Xiaowei Zheng (Geosciences Journal, 2019)

Spatial distribution, source identification, and potential risk assessment of toxic contaminants in surface waters from Yulin, China - Jing Liu; Yongjun Liu; Aining Zhang; Yu Liu; Ying Zhu; Ming Guo; Rui Zhang (Environmental Monitoring and Assessment, 2019)

Diagentic features of illite in Upper Triassic Chang-7 tight oil sandstones, Ordos Basin - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Yangjinfeng Jiang; Xueqi Yang; Rui Xie (Geosciences Journal, 2019)

Numerical Simulations of Wave-Induced Soil Erosion in Silty Sand Seabeds - Zhen Guo; Wenjie Zhou; Congbo Zhu; Feng Yuan; Shengjie Rui (Journal of Marine Science and Engineering, 2019)
Silty sand is a kind of typical marine sediment that is widely distributed in the offshore areas of East China. It has been found that under continuous actions of wave pressure, a mass of fine particles will gradually rise up to the surface of silty sand seabeds, i.e., the phenomenon called wave-induced soil erosion. This is thought to be due to the seepage flow caused by the pore-pressure accumulation within the seabed. In this paper, a kind of three-phase soil model (soil skeleton, pore fluid, and fluidized soil particles) is established to simulate the process of wave-induced soil erosion. In the simulations, the analytical solution for wave-induced pore-pressure accumulation was used, and Darcy flow law, mass conservation, and generation equations were coupled. Then, the time characteristics of wave-induced soil erosion in the seabed were studied, especially for the effects of wave height, wave period, and critical concentration of fluidized particles. It can be concluded that the most significant soil erosion under wave actions appears at the shallow seabed. With the increases of wave height and critical concentration of fluidized particles, the soil erosion rate and erosion degree increase obviously, and there exists a particular wave period that will lead to the most severe and the fastest rate of soil erosion in the seabed.

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Composition of stable isotope in precipitation and its influences by different vapor sources in the eastern Qilian Mountains - Wen-xiong Jia; Xing-gang Ma; Xiu-ting Xu; Rui-feng Yuan; Dan Ding; Guo-feng Zhu (Journal of Mountain Science, 2018)

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Cascades of Ionic and Molecular Networks Involved in Expression of Genes Underpin Salinity Tolerance in Cotton - Muhammad Ali Abid; Chengzhen Liang; Waqas Malik; Zhigang Meng; Zhu Tao; Zhaoghong Meng; Javaria Ashraf; Sandui Guo; Rui Zhang (Journal of Plant Growth Regulation, 2018)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Paleogene-Neogene stratigraphic realm and tectonic-sedimentary evolution of the Qilian Mountains and their surrounding areas - LiRong Yang; JianXing Li; LePing Yue; HongLiang Wang; HuaiJun Guo; XiaoHui Zhu; Tao Zhu; Kai Du; Rui Zhang; YunXiang Zhang; HuJun Gong (Science China Earth Sciences, 2017)

Carboxyamidotriazole alleviates muscle atrophy in tumor-bearing mice by inhibiting NF-κB and activating SIRT1 - Chen Chen; Rui Ju; Lei Zhu; Juan Li; Wei Chen; De-chang Zhang; Cai-ying Ye; Lei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Novel Infection System of Recombinant BmBDV DNA into BmN Cells of Silkworm, Bombyx mori - Rui Guo; Guangli Cao; Yuexiong Zhu; Dhiraj Kumar; Renyu Xue; Yahong Lu; Xiaolong Hu; Chengliang Gong (Current Microbiology, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Uplift of the Longmen Shan area in the eastern Tibetan Plateau: an integrated geophysical and geodynamic analysis - Xiao Xu; G. Randy Keller; Rui Gao; Xiaoyu Guo; Xiaosan Zhu (International Geology Review, 2016)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Retinoic acid promotes primary fetal alveolar epithelial type II cell proliferation and differentiation to alveolar epithelial type I cells - Rui-wei Gao; Xiang-yong Kong; Xiao-xi Zhu; Guo-qing Zhu; Jin-shuai Ma; Xiu-xiang Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Spatial characteristics of development efficiency for urban tourism in eastern China: A case study of six coastal urban agglomerations - Rui Li; Qian Guo; Dianting Wu; Hongmei Yin; Hua Zhang; Taoxing Zhu (Journal of Geographical Sciences, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

Simultaneous Determination of Calycosin-7-O-β-d-Glucoside, Ononin, Calycosin, Formononetin, Astragaloside IV, and Astragaloside II in Rat Plasma After Oral Administration of Radix Astragali Extraction for Their Pharmacokinetic Studies by Ultra-Pressure Liquid Chromatography with Tandem Mass Spectrometry - Xiao-hua Liu; Jian-bang Zhao; Long Guo; Ying-lai Yang; Fang Hu; Rui-juan Zhu; Shi-lan Feng (Cell Biochemistry and Biophysics, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Identification of a novel fumarase C from Streptomyces lividans TK54 as a good candidate for l-malate production - Rui-Rui Su; Ao Wang; Song-Tao Hou; Peng Gao; Guo-Ping Zhu; Wen Wang (Molecular Biology Reports, 2014)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Metal-Binding Activity of the Soluble Recombinant Pig Metallothionein 1A Expressed in Escherichia coli - Dongbo Sun; Hong Zhang; Guojun Wu; Qinghe Zhu; Siwen Lv; Donghua Guo; Rui Wu; Jun Bao (Biological Trace Element Research, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

Genetic characterization of ticks from southwestern Romania by sequences of mitochondrial cox1 and nad5 genes - Lidia Chitimia; Rui-Qing Lin; Iustin Cosoroaba; Xiang-Yun Wu; Hui-Qun Song; Zi-Guo Yuan; Xing-Quan Zhu (Experimental and Applied Acarology, 2010)

Effects of arbuscular mycorrhizal fungi on zinnia and the different colonization between Gigaspora and Glomus - Liang-Kun Long; Qing Yao; Yong-Heng Huang; Rui-Heng Yang; Jun Guo; Hong-Hui Zhu (World Journal of Microbiology and Biotechnology, 2010)

Salicylic Acid Reduces Napropamide Toxicity by Preventing Its Accumulation in Rapeseed (Brassica napus L.) - Jing Cui; Rui Zhang; Guo Lin Wu; Hong Mei Zhu; Hong Yang (Archives of Environmental Contamination and Toxicology, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

Genetic transformation of the bast fiber plant ramie (Boehmeria nivea Gaud.) via Agrobacterium tumefaciens - Xiongfeng Ma; Chunming Yu; Shouwei Tang; Sandui Guo; Rui Zhang; Yanzhou Wang; Aiguo Zhu; Siyuan Zhu; Heping Xiong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)